Epidemiology of Listeria monocytogenes prevalence in foods, animals and human origin from Iran: a systematic review and meta-analysis - Reza Ranjbar; Mehrdad Halaji (BMC, 2018)
Abstract Background Listeria monocytogenes as the main causative agent of human listeriosis is an intracellular bacterium that has the capability to infect a wide range of cell types. Human listeriosis is a sporadic foodborne disease, which is epidemiologically linked with consumption of contaminated food products. Listeriosis may range from mild and self-limiting diseases in healthy people to severe systemic infections in susceptible populations. This study aimed to investigate the prevalence of L. monocytogenes in food resources and human samples from Iran. Methods A systematic search was performed by using electronic databases from papers that were published by Iranian authors Since January of 2000 to the end of April 2017. Then, 47 publications which met our inclusion criteria were selected for data extraction and analysis by Comprehensive Meta-Analysis Software. Results The pooled prevalence of L. monocytogenes in human origin was 10% (95% CI: 7-12%) ranging from 0 to 28%. The prevalence of L. monocytogenes in animals was estimated at 7% (95% CI: 4-10%) ranging from 1 to 18%. Moreover, the pooled prevalence of L. monocytogenes in Iranian food samples was estimated at 4% (95% CI: 3-5%) ranging from 0 to 50%. From those 12 studies which reported the distribution of L. monocytogenes serotypes, it was concluded that 4b, 1/2a, and 1/2b were the most prevalent serotypes. Conclusions The prevalence of L. monocytogenes and prevalent serotypes in Iran are comparable with other parts of the world. Although the overall prevalence of human cross-contamination origin was low, awareness about the source of contamination is very important because of the higher incidence of infections in susceptible groups.